Differences In The Occurrence Of Posterior Capsule Opacification After Polymethylmethacrylate And Foldable Acrylic Cataract Surgery - Suhartini, Suhartini; Suprayetno, Eko Dian Hadi; Winarni, Jajuk (Universitas Pahlawan Tuanku Tambusai, 2021)
Post-surgical complications include posterior capsular opacification, which reduces visual acuity. This study aims to analyze the difference in the occurrence of posterior capsular opacification after cataract surgery when installing polymethyl methacrylate and foldable acrylic intraocular lenses. The design of this study was analytical observation with a retrospective cohort comparative type. The population in this study were cataract sufferers who underwent surgery with the installation of polymethyl methacrylate and foldable acrylic lenses at the Undaan Eye Hospital, Surabaya. The sample of 119 people was selected using non-probability sampling with a purposive sampling approach. The instrument in this research used an observational sheet. Data were analyzed using the Mann-Whitney test. The results showed that the majority of Posterior Capsular Opacification using the Polymethyl Methacrylate method was mostly normal, namely 11 respondents (61.1%), while most of the Posterior Capsular Opacification using the Foldable Acrylic Cataract Surgery method was almost normal, namely 7 respondents (38.9%) . The results of further analysis showed that there was no significant difference in Posterior Capsular Opacification between the Polymethyl Methacrylate and Foldable Acrylic Cataract Surgery methods (p-value = 0.748; α <0.05). Cataract surgery methods with Polymethyl Methacrylate and Foldable Acrylic Cataract Surgery do not affect the results of post-operative visual acuity even though the incisions caused by the method are different. Postoperative visual acuity can be influenced by many things, both intrinsic and extrinsic.